Screening nostalgia : populuxe props and technicolor aesthetics in contemporary American film - Sprengler, Christine (Berghahn Books, 2009)
In this fascinating in-depth study of the impact of nostalgia on contemporary American cinema, Christine Sprengler unpicks the history of the concept and explores its significance in theory and practice. She offers a lucid analysis of the development of nostalgia in American society and culture, navigating a path through the key debates and aligning herself with recent attempts to recuperate its critical potential. This journey opens up the myriad permutations of nostalgia across visual and material culture and their interface with cinema, with the 1950s emerging as a privileged moment.
Keywords: Nostalgia in motion pictures.; Motion pictures -- Aesthetics.; Motion pictures -- United States -- History -- 20th century.; Nostalgie au cinéma.; Cinéma -- Esthétique.; Cinéma -- États-Unis -- Histoire -- 20e siècle.; ART -- Film & Video.; PERFORMING ARTS -- Film & Video -- Reference.; PERFORMING ARTS -- Film & Video -- Direction & Production.; Motion pictures; Motion pictures -- Aesthetics; Nostalgia in motion pictures; United States; 1900-1999; History